PROPORTIZATION OF PERSONAL DATA IN THE EUROPEAN LEGAL ORDER - Hasanova, Arzu (My University, 2020)
The GDPR, applied since 2018, has largely filled the gaps and shortcomings in personal data protection that existed under the 1995 Directive. However, additional measures are still needed to further harmonize the protection of personal data, as well as to correct the imbalance of power between data subjects and controllers. One of the options for providing real control of data subjects over personal data is a property regime, which by its nature implies the most complete right that has a binding effect on any third parties. The proportization approach was developed in American doctrine as an alternative to the tort system with limited application, and as a way to avoid a biased legislative process that reflected primarily the interests of lobbying companies. This study provides an in-depth analysis of the control tools that are already applied in the EU legal system. These tools are compared with the objectives of the Regulation and the prospects for their achievement by the already available mechanisms. It is done to assess how if property regime on personal data can provide something valuable for personal data protection purposes and if the property regime is (in)capable of resolving the set objectives in the context of the European legal order.
Keywords: personal data protection, data ownership, control over personal data, consent of data subject, fundamental right to personal data protection, empowerment of data subject, fair data processing